Application of Arbuscular Mycorrhizal Fungi to Increasing N-total and P- Available Soil for Eggplant (Solanum melongena l.) Growth on Ultisol Soil - Ferdi Ferdi; Husna Husna; Namriah Namriah; Darwis DEA; Zulfikar Zulfikar; Resman Resman (Journal of Tropical Mycorrhiza, 2023)
Ultisol land is a physically and chemically poor piece of land because it needs special handling that must be done with extreme caution. Arbuscular mycorrhizal fungi (AMF) is one biological fertilizer technique to get around this issue. One of the tiny soil creatures that can coexist with the roots of land plants is the arbuscular mycorrhizal fungi. In order to support plant development and make it simpler for plants to absorb nutrients and maintain soil moisture, AMF can symbiose with plant roots and form hifa around young roots. The purpose of this study is: (1) to determine the effect of the application of the AMF on increasing N-total and P-available on ultisol soil, (2) to determine the effect of the best AMF application on the growth of eggplant in Ultisol. This research was conducted on experimental land II and the Laboratory of AMI branch of Sultra. The study was conducted in November 2022- January 2023. This study used a group of randomized groups. Arbuscular mycorrhizal fungi consists of 5 levels, namely M0 = without treatment (control), M1 = 5 g , M2 = 10 g , M3 = 15 g , and M4 = 20 g polybag-1. The results of the study show that the AMF affected the total increase in N and P-available ultisol soil, the results of the initial analysis of 0.03% increased to 0.13% and P available from 9.00 ppm increased to 17.50 ppm. AMF with a dose of 20 g  polybag-1 provides better eggplant plant growth.